2000
DOI: 10.1128/iai.68.2.767-778.2000
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Genes Encoding Antigen 85A and Antigen 85B of Mycobacterium tuberculosis H37Rv: Effect on Growth in Culture and in Macrophages

Abstract: The mechanism of pathogenesis of Mycobacterium tuberculosis is thought to be multifactorial. Among the putative virulence factors is the antigen 85 (Ag85) complex. This family of exported fibronectin-binding proteins consists of members Ag85A, Ag85B, and Ag85C and is most prominently represented by 85A and 85B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
178
1
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(189 citation statements)
references
References 34 publications
2
178
1
8
Order By: Relevance
“…In an attempt to create Mtb derived vaccine strain with a potential to undergo phagosome lysosome fusion, Saikolappan et al [25] generated a double knock out (DKO) strain, by deleting the genes fbpA and sapM in Mtb (DfbpADsapM). They had previously reported that the disruption of fbpA (Ag85A) gene from Mtb resulted in the attenuation of the mutant within the macrophages [27]. Using THP1 macrophages they demonstrated that the DKO mutant showed higher attenuation as the mutant pathogen was unable to inhibit phagosome lysosome fusion in the infected host cell.…”
Section: Sapmmentioning
confidence: 99%
“…In an attempt to create Mtb derived vaccine strain with a potential to undergo phagosome lysosome fusion, Saikolappan et al [25] generated a double knock out (DKO) strain, by deleting the genes fbpA and sapM in Mtb (DfbpADsapM). They had previously reported that the disruption of fbpA (Ag85A) gene from Mtb resulted in the attenuation of the mutant within the macrophages [27]. Using THP1 macrophages they demonstrated that the DKO mutant showed higher attenuation as the mutant pathogen was unable to inhibit phagosome lysosome fusion in the infected host cell.…”
Section: Sapmmentioning
confidence: 99%
“…Removal of TDM from the surface of M. tuberculosis results in enhanced trafficking to acidic vesicles and decreased survival of the organism within macrophages (Indrigo et al, 2002(Indrigo et al, , 2003. Relative to surface-associated TDM, organisms genetically altered to produce less TDM, or irregular TDM, exhibit reduced growth and survival both in vivo and in vitro (Armitige et al, 2000;Copenhaver et al, 2004;Glickman et al, 2000;Rao et al, 2005). Perhaps TDM's most interesting attribute is its ability to induce cytokine and chemokine production leading to granuloma formation in the lungs of responsive mice (Behling et al, 1993;Bekierkunst, 1968;Guidry et al, 2004;Lima et al, 2001;Perez et al, 2000;Yamagami et al, 2001).…”
mentioning
confidence: 99%
“…Although individual knock-out strains for each isoform have been generated (21,22), the triple knock-out ag85ABC in M. tuberculosis has not been reported, presumably because this is lethal. Because of the apparent ability of the Ag85 enzymes to complement each other, at least as assessed by their ability to continue to grow in vitro (23,24), individual mutants have thus far failed to fully dissect the functional roles of the Ag85s in cell envelope biogenesis.…”
mentioning
confidence: 99%